posted by Nashea

1. -1+1=0?
2. 2x(-4)x(-4)x(-2)=-8 or 64
on this one i am not sure if i multiply the absolute value or multiply as is

  1. PsyDAG

    1. Yes

    2. I don't know if you have the formula correctly written. Online we use an asterisk (*) to indicate multiplication rather than x, because x is often used to indicate an unknown. If your x's indicate multiplication:

    2(-4) * (-4)(-2) = -8 * 8 = -64

    I hope this helps. Thanks for asking.

Respond to this Question

First Name

Your Answer

Similar Questions

  1. math

    how do i do x2+12x+32 x2+12x = 14x+32 subtract 14x from each side 14x=32 divide by 2 7x=16 x=16/7, which is 2 and 2/7 ok maybe you typed that question wrong?
  2. someone help

    my post is still on this page as algebra, could someone elaborate on what bobpursley tried to help me with. See your original post. I am guessing you are referring to your question 5)Simplify:(5x-4)^2 and your answer= 25x^2 - 16 (5x-4)^2 …
  3. pre-algebra

    Ok, so this is about absolute value function and I was wondering in this: y= 2|2| +1 would you multiply the 2s?
  4. Math

    Multiply (1-5x³)² I am not sure If I add or multiply the exponents would this be solved as 1-5x^6?
  5. Algerbra 1

    1 15-4.10-14 2 9x-18=54 x= 3 Multiply 8/9(b-72) 4 Solve using the multiplication principle -10x=260 solution for x= 5 Multiply 3.(-5.(-3).(-10)=
  6. Math(Please respond)

    .50 - x / x = 3.20e-1 I need to solve for x. I was going to do .50 X 3.20e-1 and then take the square root but this is not correct. I am not sure what to do. Thank you for your help. Math(Please help) - Reiny, Tuesday, April 17, 2012 …
  7. algebra

    Solve. x/9-1/7=26/63 STEP 1: The LCM is _________ To clear denominators, multiply each side of the equation by the LCM. _______/1 (x/9-1/7)=__________/1 multiply 26/63. STEP 2: Use the Distributive Property. _____/1 multiply x/9 - …
  8. Math, Please Help!

    Ned divided a given number by 3 and then added 2. If he should have multiplied the number by 3 and then subtracted 2, which of the following two steps can he do next to get the correct answer?
  9. Algebra 1

    I pretty much know this problem 4y+2x=18 3x+6y=26 multiply -3= -6x+-12y= -54 multiply 2 = 6x+-12= 52 The answer is -2 but I am not sure what to do next since both x and y were canceled out.
  10. Math

    A student is trying to solve the set of two equations given below: Equation A: x + z = 6 Equation B: 2x + 4z = 1 Which of the following is a possible step used in eliminating the z-term?

More Similar Questions